Critical Role of Astrocyte NAD + Glycohydrolase in Myelin Injury and Regeneration - Langley, Monica R.; Choi, Chan-Il; Peclat, Thais R.; Guo, Yong; Simon, Whitney L.; Yoon, Hyesook; Kleppe, Laurel; Lucchinetti, Claudia F.; Chini, Claudia C. S.; Chini, Eduardo N.; Scarisbrick, Isobel A. (The Journal of neuroscience, 2021)
Western-style diets cause disruptions in myelinating cells and astrocytes within the mouse CNS. Increased CD38 expression is present in the cuprizone and experimental autoimmune encephalomyelitis models of demyelination and CD38 is the main nicotinamide adenine dinucleotide (NAD + )-depleting enzyme in the CNS. Altered NAD + metabolism is linked to both high fat consumption and multiple sclerosis (MS). Here, we identify increased CD38 expression in the male mouse spinal cord following chronic high fat consumption, after focal toxin [lysolecithin (LL)]-mediated demyelinating injury, and in reactive astrocytes within active MS lesions. We demonstrate that CD38 catalytically inactive mice are substantially protected from high fat-induced NAD + depletion, oligodendrocyte loss, oxidative damage, and astrogliosis. A CD38 inhibitor, 78c, increased NAD + and attenuated neuroinflammatory changes induced by saturated fat applied to astrocyte cultures. Conditioned media from saturated fat-exposed astrocytes applied to oligodendrocyte cultures impaired myelin protein production, suggesting astrocyte-driven indirect mechanisms of oligodendrogliopathy. In cerebellar organotypic slice cultures subject to LL-demyelination, saturated fat impaired signs of remyelination effects that were mitigated by concomitant 78c treatment. Significantly, oral 78c increased counts of oligodendrocytes and remyelinated axons after focal LL-induced spinal cord demyelination. Using a RiboTag approach, we identified a unique in vivo brain astrocyte translatome profile induced by 78c-mediated CD38 inhibition in mice, including decreased expression of proinflammatory astrocyte markers and increased growth factors. Our findings suggest that a high-fat diet impairs oligodendrocyte survival and differentiation through astrocyte-linked mechanisms mediated by the NAD + ase CD38 and highlights CD38 inhibitors as potential therapeutic candidates to improve myelin regeneration. SIGNIFICANCE STATEMENT Myelin disturbances and oligodendrocyte loss can leave axons vulnerable, leading to permanent neurologic deficits. The results of this study suggest that metabolic disturbances, triggered by consumption of a diet high in fat, promote oligodendrogliopathy and impair myelin regeneration through astrocyte-linked indirect nicotinamide adenine dinucleotide (NAD + )-dependent mechanisms. We demonstrate that restoring NAD + levels via genetic inactivation of CD38 can overcome these effects. Moreover, we show that therapeutic inactivation of CD38 can enhance myelin regeneration. Together, these findings point to a new metabolic targeting strategy positioned to improve disease course in multiple sclerosis and other conditions in which the integrity of myelin is a key concern.